PREVALENCE OF CONGENITAL AND HEREDITARY ENT PATHOLOGIES IN THE REPUBLIC OF UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2025)
This study aimed to systematize data from 2014–2025 on the prevalence of congenital and hereditary ENT disorders in the Republic of Uzbekistan (RUz), focusing on congenital/hereditary hearing loss and craniofacial anomalies affecting the ENT system (cleft lip and palate), along with a brief review of rare congenital anomalies of the nose and larynx. Results: Confirmed neonatal hearing impairment is 3.3 per 1,000 live births (0.33%), exceeding typical global estimates in countries with established universal newborn hearing screening (UNHS) programs. Approximately 50–60% of childhood hearing loss is of genetic origin. In Karakalpakstan, the incidence of cleft lip and/or palate during 2017–2021 ranged between ~0.76 and ~1.3 per 1,000 live births; previous estimates were 1:700–1:850. Approximately 22,000 individuals live with hearing impairment nationwide, supported by 20 specialized boarding schools (2020–2021). Since 2023, a national UNHS program has been implemented alongside expansion of cochlear implantation. Consanguinity remains a significant background factor, contributing to a substantial proportion of congenital anomalies. Conclusions: Scaling up UNHS, expanding molecular genetic diagnostics, and establishing national registries are essential to reduce early disability and improve speech and cognitive outcomes in affected children.